The experience of prevention of dacryocystitis recurrences in external dacryocystorhinostomy - D. Sh. Shikhunov; A-G. D. Aliev; A. A. Aliev; A. B. Abdulaev (Российский офтальмологический журнал, 2018)
Purpose: to evaluate the effectiveness of integrated methods of prevention dacryocystitis recurrences in external dacryocystorhinostomy. Materials and methods. 120 patients (120 eyes) with dacryocystitis, 85 women and 35 men, aged 21 to 75, were divided into 2 groups. The main group of 60 patients (60 eyes, 40 women and 20 men) whose mean age was 65 ± 12.5 years were subjected to external dacryocystorhinostomy with the use of a specially modified device, trepanation fraise, for the formation of the bone window and a binary stent to ensure the tamponade of a formed anastomosis. The control group was formed by the remaining 60 patients (60 eyes, 45 women and 15 men) with a mean age of 69 ± 16.2 years, who underwent regular operations according to Addeo Toti. Results. In the main group, recuperation was noted in 49 cases (82 %) and improvement in 10 cases (17 %). 1 case (1.6 %) showed a recurrent dacryocystitis. In the control group, recuperation was achieved in 38 cases (63.3 %), improvement in 17 cases (28.3 %) and the recurrence of the condition occurred in 5 cases (8.3 %). Conclusion. The proposed method enables an effectiveness increase of external dacryocystorhinostomy surgeries. For citation: Shikhunov D.Sh., Aliev A-G.D., Aliev A.A.-G., Abdulaev A.B.. The experience of prevention of dacryocystitis recurrences in external dacryocystorhinostomy. Russian ophthalmological journal. 2018; 11 (1): 30-4. doi: 10.21516/2072-0076-2018-11-1-30-34 (In Russian).